Review and analysis of the 2008 National Stocker Survey - Roe, Janell (Kansas State University, 2011)
The 2008 National Stocker Survey defines the backgrounding/stocking of cattle as ―operations where calves are grown after weaning and/or preconditioning but before the feedlot. This includes calves purchased for this purpose as well as those retained by cow-calf producers post-weaning, but before marketing or retention through the feedlot. Backgrounding offers many benefits to farmers including, but not limited to, adding value to their feedstuffs—hay, grain, etc.—by feeding it to their cattle and potentially spreading risk by increasing marketing time or engaging in contracts with feedlots. However, producers also take on increased costs as it takes more time to wean, bunk-train, vaccinate, etc. compared to other operations in the cattle industry. This thesis attempts to analyze two studies using the 2008 National Stocker Survey. The first is how producer and operation characteristics—producer age, type of operation, income derived from backgrounding—relate to why producers find variables such as cattle prices, animal health management, marketing practices, and nutrition important. The second is how producer and operation characteristics relate to producers that use futures market contracts and options on futures. Binary and ordered logit models were used to find the statistical significance of the aforementioned studies.Since this survey was specifically designed to profile the stocking/backgrounding industry, some of the estimated models did not add a lot of value beyond the summary statistics for the various dependent variables. That is, the ordered logit models did not identify any strong relationships given that almost all of the producers that responded to these questions found feeder cattle prices, animal health management, marketing practices, and nutrition very important, which can be seen by analyzing the summary statistics. In addition, the binary logit models that were used for the futures market contract and options on futures models, found that the best way to pinpoint producers using either futures contracts or options was if producers were already using risk management strategies. Therefore, the survey’s purpose of profiling the stocker industry may be its best use.
Keywords: Stocking cattle; Backgrounding cattle; Options; Futures contracts; Animal Sciences (0475); Economics, Agricultural (0503)